Handling Case By Investigator To Action Criminal Speech Hatred - Ardyanzah, Muhammad; Rahman, Abdul; Anzar, Anzar (Faculty of Law, Universitas Muslim Indonesia, 2025)
The purpose of this research is to identify and explain the enforcement of law against hate speech crimes and to determine the factors influencing hate speech. This study employs an empirical legal research method, which examines various aspects in data collection related to hate speech crimes. The findings of this research indicate that the examination process for perpetrators at the police department differs from other cases. The results show that law enforcement against hate speech crimes at the Makassar City Police Resort is carried out through several stages: report reception, investigation, statement collection, evidence gathering, and suspect determination. Investigators must adhere to applicable legal procedures and regulations. The investigators of the Makassar City Police Resort take preventive measures against hate speech crimes through legal education campaigns, social media monitoring, community cooperation, and reporting services. These actions are conducted based on Law No. 11 of 2008 concerning Information and Electronic Transactions (ITE Law).